Macbeth - Shakespeare, William, 1564-1616; Royal Shakespeare Company (Oxford, England, UK : Oxford University Press, 2017)
This full-colour edition includes the RSC's active approach to exploring Macbeth - the text, vibrant RSC performance photographs, page summaries, glosses, contextual information and much more. It aims to motivate and inspire students in their early encounters with Shakespeare's plays whilst giving students confidence for all stages of their study of Shakespeare.
HS
"RSC Royal Shakespeare Company"
Adolescent.
Text in English
Keywords: Shakespeare, William, -- 1564-1616.; Macbeth, -- King of Scotland, -- active 11th century -- Drama; English drama (Tragedy).; Scotland -- Kings and rulers -- Drama; Scotland -- History -- To 1057 -- Drama